«RESETTLEMENT IN ISTANBUL» - Aigul T. Dzhumagulova (Современная наука и инновации)
This article is intended to make the analysis and comparison of the Nogai historical epic with real historical events from the life of the Nogais, the example of the song «Resettlement in Istanbul»